Finding new lanes: Chimeric antigen receptor (CAR) T‐cells for myeloid leukemia - Pratap, Suraj (Cancer Rep (Hoboken), 2020)
BACKGROUND: Myeloid leukemia represents a heterogeneous group of cancers of blood and bone marrow which arise from clonal expansion of hematopoietic myeloid lineage cells. Acute myeloid leukemia (AML) has traditionally been treated with multi‐agent chemotherapy, but conventional therapies have not improved the long‐term survival for decades. Chronic myeloid leukemia (CML) is an indolent disease which requires lifelong treatment, is associated with significant side effects, and carries a risk of progression to potentially lethal blast crises. RECENT FINDINGS: Recent advances in molecular biology, virology, and immunology have enabled researchers to grow and modify T lymphocytes ex‐vivo. Chimeric antigen receptor (CAR) T‐cell therapy has been shown to specifically target cells of lymphoid lineage and induce remission in acute lymphoblastic leukemia (ALL) patients. While the success of CAR T‐cells against ALL is considered a defining moment in modern oncology, similar efficacy against myeloid leukemia cells remains elusive. Over the past 10 years, numerous CAR T‐cells have been developed that can target novel myeloid antigens, and many clinical trials are finally starting to yield encouraging results. In this review, we present the recent advances in this field and discuss strategies for future development of myeloid targeting CAR T‐cell therapy. CONCLUSIONS: The field of CAR T‐cell therapy has rapidly evolved over the past few years. It represents a radically new approach towards cancers, and with continued refinement it may become a viable therapeutic option for patients of acute and chronic myeloid leukemia.